Adapting & preserving through sturdy journey to create a new normal: a phenomenological insight into factors affecting medical resident’s journey to consultant practice - Sohail, Marium; Yasmin, Rahila; Rauf, Haris (Journal of the Pakistan Medical Association, 2022)
Objective: To explore factors promoting and hampering a medical resident’s journey from residency induction to role adaptation into consultant practice. Method: The qualitative, phenomenological study was conducted at the Fatima Memorial Hospital and Sir Ganga Ram Hospital, Lahore, Pakistan, from February to July 2019, and comprised junior residents, senior residents, newly qualified consultants and supervising consultants from four departments. Semi-structured interviews were conducted to achieve theoretical saturation. The interviews were audio-recorded, transcribed verbatim, and along with nonverbal cues notes by the researchers were analysed using Atlas.ti 7. Using interpretive phenomenological analysis protocol, codes were merged into categories to form main themes. Results: Of the 16 subjects, 4(25%) each were junior residents, senior residents, senior registrars and supervising consultants. There were 7(44%) males and females 9(56%) females. The mean age of the residents was 30.9+5.03 years and that of the supervisors was 55.3+0.97 years. Overall, 157 codes were developed which led to 18 categories and subsequently to 2 main themes; intrinsic factors and extrinsic factors. The former encompassed physical and emotional health, personality traits, style, personal skills, core knowledge, attribution training, self-selection of career, and previous life experiences. Extrinsic factors included physical/non-physical environment, economic stability, communication of expectations, structured residency programme, regular programme evaluation, society and culture, family, support system, preparation for transition, psychological assistance, role of supervisor, involvement into communities of practice, time for relaxation, opportunity provision, work-life boundaries, and reflective practices. —Continue